The identity of a new profession: examining the aegis of Traditional Chinese Medicine - Le, Brenda (My University, 2019)
In recent decades, the rapidly growing practices of acupuncture and Chinese herbal medicine have become professionalised under the banner of Traditional Chinese Medicine (TCM) in Canada. Many consider TCM to be a catch-all term representing the medical theories and practices developed over thousands of years in China. Beyond this broad description, Canadian sources of information lack a comprehensive definition of what TCM is (or is not), and there is little to no discussion of this topic within the discipline. Our study investigates the historical precedents leading up to the formal creation of “Traditional” Chinese Medicine, and how this relates to education, practice and regulation of this new profession in Canada.
Presented on April 23, 2019 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: Traditional Chinese Medicine; theory and practice; Canada